Integrating Islamic Hisab Concepts and Probability Theory in Mathematics Learning: A Contextual Study in Indonesian Islamic Boarding Schools - Sari, Alfizah Ayu Indria; Lutfi, Ahmad (Ahlussunnah: Journal of Islamic Education, 2025)
This study aims to explore teachers’ and students’ perceptions and experiences in integrating Islamic hisab concepts into the teaching of probability theory at Pondok Pesantren Modern Nurul Ikhlas. Employing a qualitative approach with an interpretative phenomenological design, the research involved two mathematics teachers and six eleventh-grade students as participants. Data were collected through classroom observations, in-depth interviews, and document analysis. The instruments included an observation checklist, semi-structured interview guidelines, and a document analysis sheet. The findings reveal that hisab integration remains partial and largely dependent on teachers’ initiatives. Students perceived mathematics lessons with hisab integration as more relevant and motivating, although the lack of structured resources and practical guidelines hindered its consistent application. The study concludes that curriculum development, teacher training, and institutional support are essential to ensure that hisab integration in probability learning is implemented systematically and sustainably.